Observations on “inan-” in Hittite Cuneiform Texts - Z. Nihan Kırçıl (Anadolu Araştırmaları)
In Hittite cuneiform texts, the word inan- has meanings encompassing a certain disease, mental illness, discomfort, malaise, trouble. Unfortunately, there is no specific definition of the word inan-, which appears in various sources including prayers, rituals, and medical texts. The exact symptoms of this disease are not given in any of these sources. However, the clues given by the usages of the word inan- in a medical text and a Zuwi ritual suggest that it may have been related to a skin disease, though this is not conclusive, and more evidence is necessary to confirm this. This article also examines other texts in which the word inan- occurs and the effects and treatments of inan- disease that are discussed in these sources. In addition, evidence from magic rituals demonstrates that various adjectives were used for the Sun God, and according to the Ayartaša rituals that are discussed in this study, it is apparent that one of the epithets of the Sun God may have been the word inan-.